2010
DOI: 10.1016/j.maturitas.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer: An update in diagnosis, treatment and molecular profiling

Abstract: Significant advances have been made in the diagnosis and treatment of female breast cancer, resulting in a decline in incidence and a global improvement in clinical outcome. The statistics for male breast cancer (MBC) stand in sharp contrast – over the past several decades, there has been a steady rise in the incidence of this disease, and clinical outcome has improved at a much slower pace. In the current review, the clinicopathologic features of MBC are described in detail. An emphasis is placed on molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 78 publications
1
43
0
4
Order By: Relevance
“…The most frequent histological diagnosis was invasive ductal carcinoma (IDC) in >85% as compared to (85-95%) rate of IDC in the literature (Dnami et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…The most frequent histological diagnosis was invasive ductal carcinoma (IDC) in >85% as compared to (85-95%) rate of IDC in the literature (Dnami et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…OALib Journal breast cancer may be higher (30% -56%) [45], while others report rates of HER-2 overexpression lower (2% -18%) [46] [47]. According to Park et al [48], out of 10 Korean patients with breast cancers, five (50%) demonstrated HER-2 overexpression.…”
Section: /17mentioning
confidence: 99%
“…Male breast cancer has a higher (over 90%) hormone receptor expression and, as a consequence, reacts more effectively to endocrine therapy [6,16,17,19,22,23,24,25,26,27].…”
Section: Abstract: Male Breast Cancer Basal Markers Mesenchymal Mamentioning
confidence: 99%
“…Besides, the prognosis for male breast cancer is worse [5,18,20,21]. A study by Baojiang et al of 5-year survival rates of patients suffering from male breast carcinoma and female breast carcinoma produced the following results: 61.2% and 68.7% (DFS), and 75.% and 82.9% (OS), respectively [20].Male breast cancer has a higher (over 90%) hormone receptor expression and, as a consequence, reacts more effectively to endocrine therapy [6,16,17,19,22,23,24,25,26,27].The treatment of male breast carcinoma is based on standard methods, more specifically surgical procedures [6, 21, 25, …”
mentioning
confidence: 99%